Microfinance 3.0 Reconciling Sustainability with Social Outreach and Responsible Delivery - Köhn, Doris (Springer Nature, 2013)
Development Economics; Macroeconomics/Monetary Economics//Financial Economics; Finance, general; Business Strategy/Leadership; Ethics; Economic Growth; Microfinance; Development Finance; Sustainable Development; Good Corporate Governance; Interest Rates; Sustainability